2021
DOI: 10.1038/s41598-021-97886-0
|View full text |Cite
|
Sign up to set email alerts
|

Calorimetry, physicochemical characteristics and nitrogen release from extruded urea

Abstract: Our hypothesis was that extrusion of urea associated with corn may reduce N solubilization and increase the nutritional quality of this food for ruminants. We aimed to physically and chemically characterize a corn and urea mixture before and after the extrusion process. It was evaluated morphological differences by scanning electron microscopy, nitrogen solubilization, and compound mass loss by thermogravimetry. In scanning electron microscopy, extruded urea showed agglomerated and defined structures, with cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…The UE is a product obtained by extruding a mixture of starch and urea, by means of high temperature and pressure, leading to the gelatinization of the starch. Extrusion causes the incorporation of urea into the starch structure, reducing its solubility 6 , 11 , 12 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The UE is a product obtained by extruding a mixture of starch and urea, by means of high temperature and pressure, leading to the gelatinization of the starch. Extrusion causes the incorporation of urea into the starch structure, reducing its solubility 6 , 11 , 12 .…”
Section: Discussionmentioning
confidence: 99%
“…For example, a study 5 found that coating of urea chitosan did not bring significant effect on pH, dry matter and organic matter digestibility, microbial protein synthesis, and amonia concentration in the rumen. On the other hand, some authors 6 cite that the extrusion of urea with corn, in addition to controlling the release of nitrogen, improves the use of urea due to a better synchronization during the degradation of these ingredients.…”
Section: Introductionmentioning
confidence: 99%
“…Extruded urea is the product resulting from the extrusion of a mixture of starch, urea (200% crude protein) and sulfur (3.2% S) by means of high temperature and pressure, leading to the gelatinization of starch (Kozerski et al, 2021a). In this type of processing, the starch granules are gelatinized, and the urea modified from a crystalline structure to a non-crystalline form, with most of the non-crystalline structures found within the gelatinized portion, making it more palatable than grain mixtures of unprocessed urea, allowing the food to be better accepted by animals (Kozerski et al, 2021a).…”
Section: Introductionmentioning
confidence: 99%
“…Extruded urea is a product obtained by subjecting a mixture of starch (22% total digestible nutrients, TDN), urea (200% crude protein), and sulfur (3.2% S) to high temperature and pressure, resulting in starch gelatinization 11 . This processing method facilitates a gradual release of nitrogen in the rumen 11 . Moreover, it synchronizes nitrogen release with starch, promoting increased microbial protein production.…”
Section: Introductionmentioning
confidence: 99%